Bombardment of the surface by a low-energy ion flow accelerated in the near-surface layer of the space charge - Hrechkо, Ya.; Babenko, Ie.; Sereda, I.; Azarenkov, N. (Problems of Atomic Science and Technology, 2023)
The paper presents a method for the formation of low-energy ion flow for creation and treatment of functional coatings without radiation damage. Plasma source based in arc discharge with filament cathode creates the primary plasma in the volume of vacuum chamber where the treated sample is placed. The formation of low-energy ion flow takes place in the layer of space charge near the samples surface. The behavior of the ion current density depending on the potential drop in the layer has been studied for various experimental parameters and conditions. The sample surface treatment by low-energy ion flow has been also evaluated. Представлено спосіб формування низькоенергетичного потоку іонів для створення та обробки функціональних покриттів без радіаційних пошкоджень. Джерело плазми на основі дугового розряду з катодом розжарення створює первинну плазму в об’ємі вакуумної камери, де розміщується зразок, що обробляється. Формування низькоенергетичного потоку іонів здійснюється у шарі просторового заряду біля поверхні зразків. Досліджено поведінку густини іонного струму в залежності від падіння потенціалу в шарі для різних експериментальних параметрів і умов. Також було оцінено обробку поверхні зразка потоком низькоенергетичних іонів.